Event processing in action - Etzion, Opher (Manning, 2011)
Unlike traditional information systems which work by issuing requests and waiting for responses, event-driven systems are designed to process events as they occur, allowing the system to observe, react dynamically, and issue personalized data depending on the recipient and situation. Event Processing in Action introduces the major concepts of event-driven architectures and shows how to use, design, and build event processing systems and applications. Written for working software architects and developers, the book looks at practical examples and provides an in-depth explanation of their architecture and implementation. Since patterns connect the events that occur in any system, the book also presents common event-driven patterns and explains how to detect and implement them. Throughout the book, readers follow a comprehensive use case that incorporates all event processing programming styles in practice today.